2010
DOI: 10.1177/112070001002000113
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Total Hip Arthroplasty with Subtrochanteric Transverse Shortening Osteotomy for Severely Dysplastic or Dislocated Hips

Abstract: Total hip arthroplasty in dislocated developmental hip dysplasia is a complex, technically demanding procedure with high complication rates. Anatomic abnormalities and the young age of the patients influence the results. Restoration of the anatomic hip center often requires shortening of the femur in order to avoid over-stretching of neurovascular structures. We performed cementless total hip arthroplasty with subtrochanteric transverse osteotomy on 44 hips in 31 patients. There were 29 female and 2 male patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…To our knowledge, this is the largest reported series in which the clinical outcomes of transverse subtrochanteric femoral shortening osteotomies performed during cementless THA in Crowe Type-III and IV DDH were evaluated. The mean Harris hip score and the mean pain component of it improved significantly in our study group similar to the results reported in the literature [1,4,6,7,20,22]. Improvement in the pre-operative limp was also significant in the majority of our patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…To our knowledge, this is the largest reported series in which the clinical outcomes of transverse subtrochanteric femoral shortening osteotomies performed during cementless THA in Crowe Type-III and IV DDH were evaluated. The mean Harris hip score and the mean pain component of it improved significantly in our study group similar to the results reported in the literature [1,4,6,7,20,22]. Improvement in the pre-operative limp was also significant in the majority of our patients.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, they mentioned that graft application did not have a significant contribution to stability. Yalcin et al reported that they did not use plate-screw stabilization when good initial rotational stability was obtained by the femoral component, but they used low contact plates and screws primarily when rotational stability was in doubt [7]. However, they observed 5 non-unions in patients whose osteotomies were not stabilized with plates.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations